2018
DOI: 10.1002/14651858.cd013189
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography for diagnosing skin cancer in adults

Abstract: Background Early accurate detection of all skin cancer types is essential to guide appropriate management and to improve morbidity and survival. Melanoma and squamous cell carcinoma (SCC) are high-risk skin cancers, which have the potential to metastasise and ultimately lead to death, whereas basal cell carcinoma (BCC) is usually localised, with potential to infiltrate and damage surrounding tissue. Anxiety around missing early cases needs to be balanced against inappropriate referral and unnecessary excision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
10

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 190 publications
2
81
0
10
Order By: Relevance
“…The OCT device in combination with reflectance confocal microscopy imaging has shown great sensitivity and specificity to detect BCC [10,11]. A recent study reported the sensitivity and specificity of the OCT devices' ability to detect BCC to be 95% and 77%, respectively [12]. The same capabilities are also used for defining pathologic skin margins prior to surgery and monitoring the skin progress following non‐invasive treatments [13–16].…”
Section: Clinical Use Of Oct In Sun‐damaged Skin and Skin Cancermentioning
confidence: 99%
“…The OCT device in combination with reflectance confocal microscopy imaging has shown great sensitivity and specificity to detect BCC [10,11]. A recent study reported the sensitivity and specificity of the OCT devices' ability to detect BCC to be 95% and 77%, respectively [12]. The same capabilities are also used for defining pathologic skin margins prior to surgery and monitoring the skin progress following non‐invasive treatments [13–16].…”
Section: Clinical Use Of Oct In Sun‐damaged Skin and Skin Cancermentioning
confidence: 99%
“…The rest top 10 co-cited references including methodology studies (20,25) , epidemiological data of cancer (24) , and the reporting guideline of systematic reviews (26) . The latest co-cited references were focused on the diagnosis and treatment of skin cancer in adults (43)(44)(45) . All these co-cited references constituted the knowledge base of this field.…”
Section: Citation Informationmentioning
confidence: 99%
“…For example, the differentiation of melanocytes from langerhans cells in melanocytic lesions lacks specificity, the misdiagnosis due to specific lesion or missed detection because of sampling error, as well as the clinical experience of the doctors (63) . There were four records in Cancer-CSR concentrated on the applying of RCM for diagnosing skin cancer in adults with any suspicious lesion which was all published in 2018 (64)(65)(66)(67) .…”
Section: Research Hotspotsmentioning
confidence: 99%
“…7 However, many review papers manifest the lack of study in cutaneous SCC. [8][9][10] In this work, we focus on SCC detection.…”
Section: Introductionmentioning
confidence: 99%